Northernmost occurrence of Hemiramphus far (Actinopterygii: Hemiramphidae) in the Aegean Sea - AKCA, N.; BILECENOGLU, M. (Mediterranean Marine Science, 2010)
A new record of Hemiramphus far from the northern Aegean Sea is presented, based on a single specimen collected off Eski Foça shores, Turkey. Further individuals were observed (but not collected) in the same area, indicating an established population.